Desarrollo de variedades de papa Premium y Allipacha (2011–2018) - Andrade, H. (2025)
This presentation documents the development of two potato varieties, Premium and Allipacha, bred between 2011 and 2018 to meet agro-industrial processing requirements in Ecuador. Using CIP-derived germplasm, the program combined multilocational phenotypic selection, quality evaluation for French fry processing, resistance to late blight, and seed multiplication under university leadership. The experience highlights the importance of aligning plant breeding with market demand, strengthening seed systems, and building partnerships among universities, farmers, and the agro-food industry to improve food security and reduce dependency on imported processed potatoes.